"Rinse the Tap" Advisories Are a Refreshing Measure. Issue 5 (6th May 2019) - Burlingame, Gary A.; Masters, Sheldon V.; Przybylowicz, Joan
Abstract : When a home's plumbing has deteriorated or becomes contaminated, one option for the customer to get good, potable water is to simply refresh the water in the plumbing system.